Intestinal and extraintestinal manifestations of ulcerative colitis: correlation with Mayo scores - Mohamed Elegezy; Ola Elnagdy; Mohammed Abdelaziz; Manar Mansour; Aya Hashish; Sherine Gaafar; Noha Elnagdy (Egyptian Rheumatology and Rehabilitation)
Abstract Background Ulcerative colitis (UC) is a relapsing and remitting inflammatory bowel disease (IBD) characterized by mucosal inflammation that starts distally and can extend proximally to include the whole colon. Extraintestinal manifestations (EIMs) of UC are found in a high percentage of patients and can be more distressing than the underlying disease itself. This work aimed to analyze the intestinal and EIMs (musculoskeletal, skin, audiovestibular, and eye symptoms) in UC patients. Also, the correlations of all manifestations with activity scores (complete and endoscopic Mayo scores) have been studied. Results Of 66 patients, 58 were suffering from diarrhea and 60 had bleeding with a percentage of 87.9% and 90.9%, respectively, with different severities, while 24 had peripheral arthropathy, 14 had enthesitis, 20 had inflammatory back pain (IBP), 6 had ankylosing spondylitis (AS), 2 had erythema nodosum (EN), 36 were positively imbalanced, and 24 had abnormal pure tone audiometry (PTA) with percentages of 36.4%, 21.2%, 30.3%, 10.0%, 3%, 55.5%, and 36.4%, respectively. Also, 36.4% were suffering from sacroiliitis. No one had uveitis. For extent in number, 33.3% were E1(proctitis), 24.2% were E2 (left-sided), and 42.4% were E3 (extensive colitis). Parameters significant to complete the Mayo score (CMS) were pathology and PTA. Association between CMS with characteristics and laboratory results of UC patients showed significance to serum albumin, hemoglobin (HB) level, white blood cells (WBC), and calprotectin, while Mayo endoscopic score (MES) showed significant association with albumin, HB, calprotectin, positive C-reactive protein (CRP), weight loss, pathology, and history of exacerbation. Conclusion EIMs are prevalent among patients with UC regardless of intestinal disease activity. Few EIMs showed a significant correlation with disease activity, reflecting that bowel disease activity and systemic affection may not always occur together. This ensures the importance of clinical awareness and the necessity of a multidisciplinary, symptom-driven approach in UC management to ensure early detection and appropriate individualized treatment of EIMs.